Hubungan Kunjungan Antenatal Care (ANC) dengan Kejadian Komplikasi Obstetri di Indonesia : Analisis Data Sekunder Survei Demografi dan Kesehatan Indonesia (SDKI) Tahun 2017 - Mondastri Korib Sudaryo; Aini Qur'ani Sam (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: More than 500,000 mothers died each year due to complications in pregnancy. Even though obstetric complications become unpredictable events and caused more than 90% of maternal deaths at or around delivery. Therefore, the approach taken is to assume all pregnancies are risky. One of the strategies that can be used to prevent and reduce the incidence of maternal mortality in Indonesia is to find out whether there is a relationship between antenatal care (ANC) visit with the incidence of obstetric complications so that further management planning can be done more effectively in terms of lowering maternal mortality in Indonesia. Methods: This study used secondary data from the Indonesia Demographic and Health Survey (IDHS) in 2017 with a cross-sectional design. The sample in this study were mothers aged 15-49 years who had children in the last 5 years who were eligible with the inclusion criteria by taking total sampling.Result: The results of the final modeling of multivariate cox regression analysis showed that there was a relationship between ANC visit with obstetric complications with a PR value of 1.34 (95% CI 1.28-1.41) with a p-value of 0.0001. Conclusion: There is a relationship between ANC visit to obstetric complications in Indonesia after being controlled by parity and place of delivery variables.